Embedded Control Architecture for Multi-Evaporator Industrial Dehumidification Systems - Chathumal, Pamodha; Amaratunga, Sanath (PT. Teknologi Futuristik Indonesia, 2026)
Industrial dehumidification plays a pivotal role in spice processing industries, where precise moisture control directly influences product quality, shelf life, and processing efficiency. However, in many industrial facilities, these systems are operated manually or using basic on-off control methods. Such practices often result in unstable operating conditions, frequent compressor switching, increased energy consumption, and reduced equipment lifespan. This study addresses the lack of affordable, hardware-level automation for multi-evaporator systems by presenting the design and implementation of a dedicated embedded control architecture. The proposed objective was to develop a dual-microcontroller system where a primary controller manages real-time decision-making based on temperature and relative humidity, while a secondary controller is strictly dedicated to safety and time-delay protection. The system was implemented and tested in an industrial spice processing facility. Key findings demonstrate that the autonomous mode reduced outlet air temperature variation to ±1 – 2 oC and relative humidity fluctuation to ±4 – 5%, compared to significantly higher variations in manual operation. Furthermore, the system reduced operator interventions from 1-2 per shift to 0-1 and minimized compressor cycling frequency. Beyond operational efficiency, the stabilization of the drying environment directly contributes to the preservation of critical quality parameters, such as volatile oil retention and color uniformity, which are frequently compromised under manual control regimes. These results imply that low-cost embedded automation can significantly enhance operational stability and safety in agro-industrial processing without requiring expensive infrastructure upgrades.